Hydrogen production from methanol-water mixture over NiO/TiO2 nanorods structure photocatalysts - Wang, Huiqin; Jiang, Haopeng; Huo, Pengwei; Edelmannova, Miroslava Filip; Čapek, Libor; Koci, Kamila (ELSEVIER SCI LTD, 2022)
In this work, efficient NiO nanoparticles/TiO2 nanorods p-n heterojunction structure photocatalyst is constructed by reasonable design of two-step calcination technology and examined for hydrogen production activity from methanol-water mixture. In the NiO/TiO2 heterojunction structure small NiO nanoparticles are evenly distributed on the surface of TiO2 and tightly connected together with TiO2, as it was determined by microscope characterization techniques, which conducive to the interface transport of photogenerated carriers. The novelty of this paper is the detailed characterization of NiO/TiO2 photocatalysts by electrochemical technics as Transient photocurrent response, Mott-Schottky plots, linear sweep voltammograms and Electrochemical impedance spectroscopy and their correlation with photoactivity. The rationally designed NiO/TiO2 p-n heterojunction promotes the transfer of photogenerated electrons and inhibits carrier recombination. The highest hydrogen production was exhibited in the presence of the 2-NiO/TiO2 composite during 3 h of UV irradiation (701 mu mol/g(cat).), which exceeded the activity of pure TiO2 by more than 1.3 times. The loss of photocatalytic hydrogen yield is negligible after repeating cycle reactions. Finally, a possible p-n heterojunction photocatalytic reduction mechanism has been discussed and apparent quantum yield was calculated.
Produkce vodíku ze sm+ěsi metanol-voda pomocí fotokatalyzátorů NiO/TiO2 nanotyčinek
Keywords: NiO/TiO2; P-n heterojunction; composite photocatalysts; hydrogen-production; electrochemical technics; produkce vodíku; fotokatalyzátor; NiO/TiO2; nanomateriál